Roles of Curcumin and Monochromatic Light in Optimizing Liver Function to Support Egg Yolk Biosynthesis in Magelang Ducks - Kasiyati,; Sumiati,; Ekastuti, Damiana Rita; Manalu, Wasmen (International Journal of Poultry Science, 2016)
Backgroud: The biosynthesis of vitellogenin as an egg-yolk precursor in oviparous animals is occurred in the liver cells. The vitellogenin synthetic capacity of hepatocyte is under the control of estrogen that its secretion increase when the oviparous animals reach sexual maturity. This experiment was designed to study the uses of curcumin and artificial monochromatic light on liver performance to improve vitellogenin synthesis to support egg production during laying period. Materials and Methods: One hundred and ninety two female magelang ducks were assigned into a completely randomized design with a 4×4 factorial arrangement. The first factor was dose of curcumin supplementation consisted of 4 levels i.e., 0, 9, 18 and 36 mg. The second factor was the color of monochromatic light consisted of 4 levels i.e., white, red, green and blue. Results: The results showed the interaction effects between curcumin and monochromatic light on the liver weight, hepatocytes diameter, DNA and RNA concentrations in the liver cells (p